(3BOGH GdMceGA GdadGSaI GdjhfGfjjfs ((3YHO Gddg WQGO GdHjQhJi s)
(3ChdgG (B:s
(3jHOC HBOGH ajKGZhQS hehGYXg s
(3BNQgG (B:s
(3bGd MH GdZfG hGWGdJ GdGed hTOI GdMQU bjd aeG YdGeI GdYei bGd GdQchf Edi ef dGjDef bO Je GdcJGH HeYQaI Gdedc GdhgGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JGQjN fSNgG gh (B1797(3es
(3HChdg agQSJ ddeNWhW HChdg Jedc HGSe YjSi GScfOQ GdeYdha Hf Sgd GddHfGfi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdCOHs